503unc, a small and muscle‐specific zebrafish promoter. Issue 6 (26th March 2013) - Berger, Joachim; Currie, Peter D.
<x xml:space="preserve">Abstract</x> The muscle‐specific UNC‐45b assists in the folding of sarcomeric myosin. Analysis of the zebrafish unc‐45b upstream region revealed that unc‐45b promoter fragments reliably drive GFP expression after germline transmission. The muscle‐specific 503‐bp minimal promoter 503unc was identified to drive gene expression in the zebrafish musculature. In transgenic Tg(−503unc:GFP) zebrafish, GFP fluorescence was detected in the adaxial cells, their slow fiber descendants, and the fast muscle. At later stages, robust GFP fluorescence is eminent in the cardiac, cranial, fin, and trunk muscle, thereby recapitulating the unc‐45b expression pattern. We propose that the 503unc promoter is a small and muscle‐specific promoter that drives robust gene expression throughout the zebrafish musculature, making it a valuable tool for the exploration of zebrafish muscle. genesis 51:443–447. © 2013 Wiley Periodicals, Inc.